RESPON PEMBERIAN DAUN UBI JALAR UNGU (Ipomoea batatas L), DAUN MENGKUDU (Morindacitrifolia L), DAN DAUN SIRIH (Piper betle L) DALAM RANSUM TERHADAP PENAMPILAN ITIK BALI - Trisnadewi A. A. A. S.; T. G. B. Yadnya; A. A. P. P. Wibawa; I M. Mudita (Fakultas Peternakan Universitas Udayana, 2019)
The experiment was carried out to study the response of additional leaves of purple sweet potato (Ipomoea batatasL.), noni (Morinda citrifolia L.) and betle (Piper betle L.) in diets on performance of bali duck. The experimentused completely randomized design with four treatments consists of control diet A (diet without leaves), diet B (dietcontaining with purple sweet potato leaf, diet C (diet containing noni leaf), and diet D (diet containing beetle leaf).Each treatment conducted with three replications and each replications consist of five ducks. The variables observedwere feed consumption, antioxidant consumption, body gain, and FCR and of bali ducks. Feed consumption of baliducks in treatment B, C and D were significantly lower, however, the antioxidant consumption significantly higherthan control diet. In contrast, body weight gain in treatments B, C and D increased significantly but decreased FCRcompared to treatment A. The treatments of B, C, and D can increase the carcass weight, and carcass percentagesignificantly. These were offered to bali ducks could increase percentage of meat and bone but significantly decreasefat of carcass including their skin for bali ducks fed with A (control treatment). It can concluded that the leaves ofpurple sweet potato, noni, and betle leaf in diets improved the performance and carcass of bali ducks.